Health education: Development of educational material for hand-foot syndrome secondary to the use of capecitabine (Research, Society and Development, 2021)
Cancer is the main public health problem in the world. Anticancer drugs can have serious adverse reactions, many of which are potentially fatal if not properly managed. Capecitabine is a chemotherapeutic prodrug that is frequently used in the treatment of breast, colon and rectal cancer. Among the most frequent toxicities in patients undergoing capecitabine use is hand-foot syndrome (HFS). The objective this study was to develop a folder of guidelines for the prevention and treatment of HFS aimed at patients who use capecitabine in order to optimize their treatment. This is an experience report that involved three steps: problem identification; narrative literature review, layout development, illustrations and writing in folder format. The material consisted of simple guidelines, demonstrating the main signs and symptoms of HFS, in addition to a telephone number for contacting the service. Questions related to changing lifestyle habits were also included, such as improving water intake, wearing comfortable shoes and the temperature of the bath water, as well as care with the handling of cleaning products. In addition, non-pharmacological methods were mentioned, such as the use of urea-based creams, aloe vera and laser therapy. We concluded that the elaboration of the folder proposed a printed educational material that allowed a more assertive approach, aimed at the individual, clarifying their doubts and ensuring better treatment.